GABAergic changes in the thalamocortical circuit in Parkinson's disease. Issue 4 (13th November 2019) - van Nuland, Annelies J. M.; den Ouden, Hanneke E. M.; Zach, Heidemarie; Dirkx, Michiel F. M.; van Asten, Jack J. A.; Scheenen, Tom W. J.; Toni, Ivan; Cools, Roshan; Helmich, Rick C.
Abstract: Parkinson's disease is characterized by bradykinesia, rigidity, and tremor. These symptoms have been related to an increased gamma‐aminobutyric acid (GABA)ergic inhibitory drive from globus pallidus onto the thalamus. However, in vivo empirical evidence for the role of GABA in Parkinson's disease is limited. Some discrepancies in the literature may be explained by the presence or absence of tremor. Specifically, recent functional magnetic resonance imaging (fMRI) findings suggest that Parkinson's tremor is associated with reduced, dopamine‐dependent thalamic inhibition. Here, we tested the hypothesis that GABA in the thalamocortical motor circuit is increased in Parkinson's disease, and we explored differences between clinical phenotypes. We included 60 Parkinson patients with dopamine‐resistant tremor ( n = 17), dopamine‐responsive tremor ( n = 23), or no tremor ( n = 20), and healthy controls ( n = 22). Using magnetic resonance spectroscopy, we measured GABA‐to‐total‐creatine ratio in motor cortex, thalamus, and a control region (visual cortex) on two separate days (ON and OFF dopaminergic medication). GABA levels were unaltered by Parkinson's disease, clinical phenotype, or medication. However, motor cortex GABA levels were inversely correlated with disease severity, particularly rigidity and tremor, both ON and OFF medication. We conclude that cortical GABA plays a beneficial rather than a detrimental role in Parkinson's disease, and that GABA depletion may contribute to increased motor symptom expression.